Ultraviolet-B Radiation and Nitrogen Affect Nutrient Concentrations and the Amount of Nutrients Acquired by Above-Ground Organs of Maize - Carlos M. Correia; João F. Coutinho; Eunice A. Bacelar; Berta M. Gonçalves; Lars Olof Björn; José Moutinho Pereira (The Scientific World Journal)
UV-B radiation effects on nutrient concentrations in above-ground organs of maize were investigated at silking and maturity at different levels of applied nitrogen under field conditions. The experiment simulated a 20% stratospheric ozone depletion over Portugal. At silking, UV-B increased N, K, Ca, and Zn concentrations, whereas at maturity Ca, Mg, Zn, and Cu increased and N, P and Mn decreased in some plant organs. Generally, at maturity, N, Ca, Cu, and Mn were lower, while P, K, and Zn concentrations in stems and nitrogen-use efficiency (NUE) were higher in N-starved plants. UV-B and N effects on shoot dry biomass were more pronounced than on nutrient concentrations. Nutrient uptake decreased under high UV-B and increased with increasing N application, mainly at maturity harvest. Significant interactions UV-B x N were observed for NUE and for concentration and mass of some elements. For instance, under enhanced UV-B, N, Cu, Zn, and Mn concentrations decreased in leaves, except on N-stressed plants, whereas they were less affected by N nutrition. In order to minimize nutritional, economical, and environmental negative consequences, fertiliser recommendations based on element concentration or yield goals may need to be adjusted.